Draft Tenth Five Year Plan 2002-2007 Volume - I (Narrative) Government of Rajasthan - Planning Commission (Planning Commission, 2002)
Rajasthan evokes colourful image of a land of chivalrous rulers, brave and beautiful women, bedecked camels dotting the desert landscape, rich folklore and friendly people. In the last fifty years, it has emerged as the major tourist destination in India, both for the domestic and foreign tourists. Jaipur, the Pink City; Udaipur, the City of Lakes; Jaisalmer, the Dream City of ‘Sonar Kila’, (the Golden Fort), Bharatpur with its Keoladev Bird National Park are all a part of the legend of the State.
Government of Rajasthan, Planning Department